Portable Penetration Testing and Firewall Configuration Toolkit - Megat Ahmad Kamil, Megat Ahmad Izzat; Mohd Husny, Herny Ramadhani; Ya Abdullah, Norhaiza (Journal of Computing Technologies and Creative Content, 2016)
In the domain of security, a security officer must be offensive and also defensive. Being attack by attacker is not an option. They need to be creative, they have to think like them, and then only they can beat them. That is why leaning the arts of penetration testing is crucial in education level. On the other hand, let’s not forget about the basic fortress off all time that is a must to protect a network, the firewall. To possess knowledge in security, early exposure must be nurtured from undergraduate level to ease the development of knowledge and learning process for a scholar. Current scholars who are studying in security field seldom have the opportunity to exercise hands-on activity in class due to time constraint and lack of infrastructure in an educational organization. To support the initiative of providing exposure among the scholars and to overcome the aforementioned problems, an approach to develop a portable penetration testing and firewall configuration toolkit has been proposed as a learning aid for the students to perform simulation on conducting penetration testing and configuring firewall for beginners. The scholars will be able to use this proposed toolkits to perform hands-on activity at anywhere and anytime. From the proposed toolkit, scholars are able to execute basic penetration testing, network monitoring, port scanning, firewall configuration, and web and filtering. By having this proposed toolkit, the teaching and learning process will be much easier, efficient and time saving compared to conventional methods of teaching. As a conclusion, the proposed plug-and-play toolkit implements benefit user in terms of time saving, early exposure and facilitate teaching and learning session effectively.